1992
DOI: 10.1016/0378-1097(92)90064-u
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and toxicity of lipopolysaccharide from Francisella tularensis LVS

Abstract: Lipopolysaccharide (LPS) from the live vaccine strain of Francisella tularensis (F. tularensis LVS) was isolated and purified. The LPS did not stimulate lymphocytes from previously tularaemia‐vaccinated individuals or lymphocytes from nonprimed individuals. However, serum antibodies from tularaemia vaccines reacted with the LPS whereas virtually no reactivity was found with antibodies from individuals not exposed to F. tularensis LVS. Antibodies of immunoglobulin class M displayed the antibody reactivity predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
93
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 34 publications
4
93
0
2
Order By: Relevance
“…holarctica (Dreisbach et al, 2000). It is reported that the LPS is less toxic than other Gram-negative LPS (Ancuta et al, 1996;Sandstrom et al, 1992) and that its O antigen contains the rare sugars 2-acetamido-2,6-dideoxy-D-glucose (QuiNAc) and 4,6-dideoxy-4-formamido-D-glucose (Qui4NFm) and two moles of 2-acetamido-2-deoxy-D-galacturonamide (GalNAcAN), to give the repeat structure 4-AE-GalNAcAN-1,4 -AE-GalNAcAN -1,3 -â-QuiNAc -1,2 -â-Qui4NFm (Vinogradov et al, 1991). The repeat structure is similar to those found in the O antigens of Pseudomonas aeruginosa O6 and Shigella dysenteriae type 7 (Knirel et al, 1988;Vinogradov et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…holarctica (Dreisbach et al, 2000). It is reported that the LPS is less toxic than other Gram-negative LPS (Ancuta et al, 1996;Sandstrom et al, 1992) and that its O antigen contains the rare sugars 2-acetamido-2,6-dideoxy-D-glucose (QuiNAc) and 4,6-dideoxy-4-formamido-D-glucose (Qui4NFm) and two moles of 2-acetamido-2-deoxy-D-galacturonamide (GalNAcAN), to give the repeat structure 4-AE-GalNAcAN-1,4 -AE-GalNAcAN -1,3 -â-QuiNAc -1,2 -â-Qui4NFm (Vinogradov et al, 1991). The repeat structure is similar to those found in the O antigens of Pseudomonas aeruginosa O6 and Shigella dysenteriae type 7 (Knirel et al, 1988;Vinogradov et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…More recent reports indicated that purified LVS LPS was not endotoxic in D-galactosamine-sensitized mice (37) and failed to activate Limulus amoebocyte lysate (37). Further, LVS LPS also failed to stimulate human monocytes or peripheral blood lymphocytes to proliferate, produce tumor necrosis factor alpha (TNF-␣), or produce interleukin-1 (IL-1) (37). Similarly, mouse peritoneal exudate macrophages treated with LVS LPS did not produce TNF-␣ or nitric oxide, and there was no increase in surface immunoglobulin expression by a mouse pre-B-cell line in response to LVS LPS (1).…”
mentioning
confidence: 99%
“…No traditional endotoxin has been associated with virulent F. tularensis (23). More recent reports indicated that purified LVS LPS was not endotoxic in D-galactosamine-sensitized mice (37) and failed to activate Limulus amoebocyte lysate (37). Further, LVS LPS also failed to stimulate human monocytes or peripheral blood lymphocytes to proliferate, produce tumor necrosis factor alpha (TNF-␣), or produce interleukin-1 (IL-1) (37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These pathways lead to secretion of chemokines and upregulation of adhesion molecules that recruit neutrophils, monocytes, and other immune cells to the site of infection. The LPS of F. tularensis, however, is atypical and incites few proinflammatory changes in murine and human leukocytes or human endothelial cells (23)(24)(25)(26). Moreover, live F. tularensis stimulates HUVECs to secrete only low amounts of the chemokine CCL2 compared with the killed bacterium or Escherichia coli (27).…”
mentioning
confidence: 99%